Drinking Water Quality of Kathmandu Valley (Nepal Journal of Science and Technology, 2015)
This research was conducted to analyze drinking water quality of Kathmandu valley. Total 969 water samples (392 from dug wells, 287 from deep boring, 218 from treated water, 46 from tap and 26 from other water sources) received from different places of Kathmandu, Lalitpur and Bhaktapur districts during March 2012 to March 2013. These samples were analyzed for the determination of physical (pH, temperature, conductivity, turbidity), chemical (hardness, chloride, iron, arsenic, ammonia, nitrate) and microbiological (total Coliform) parameters. It was found that the temperature and nitrate were within the WHO standards while pH, conductivity, turbidity, chloride, iron, arsenic, ammonia, and Coliform bacteria exceeded the WHO standard guideline. In ground water ( well and Boring), pH, conductivity, hardness, turbidity, iron, arsenic, chloride, ammonia and total Coliform count crossed WHO standards as 5%, 2%, 0.8%, 36%, 51%, 0.1%, 2%, 11% and 86 % respectively. Hardness was within the standard in both  reated and tap water samples. Compared to treated water, pH, arsenic and chloride were within the standard in tap water. The common problematic parameters of different sources of drinking were turbidity, iron, ammonia and conductivity. Coliform bacteria were found in 36% samples of treated water whereas 80% tap water samples were contaminated from Coliform bacteria.DOI: http://dx.doi.org/10.3126/njst.v15i1.12027Nepal Journal of Science and TechnologyVol. 15, No.1 (2014) 115-120